Silvopastoral Systems in Southern South America - Peri, Pablo Luis (Springer, 2021)
This multi-authored volume contains peer-reviewed chapters from leading researchers and professionals in silvopastoral systems topic in the subtropical and temperate zones of South America (Argentina, Chile and South Brazil). It is a compendium of original research articles, case studies, and regional overviews and summarizes the current state of knowledge on different components and aspects (pasture production, animal production, trees production, carbon sequestration, conservation) of silvopatoral systems in native forests and tree plantations. The main hypothesis of the book is that farmers have integrated tree and pasture/grassland species in their land use systems to reach higher production per unit of land area, risk avoidance, product diversifi cation, and sustainability. These production systems also impact positively in main ecosystem processes. Management of these productive systems, Policy and Socioeconomic Aspects provide great opportunities and challenges for farmers and policy makers in our region. The book is unique on this subject in Southern South America and constitutes a valuable reference material for graduate students, professors, scientists and extensionists who work with silvopastoral systems.